Relation of chemical characteristics and sensory profile of catfish (Pangasius sp.) belly processed by various smoking methods - Wijaya, Fransisca; Tri Kumala Dewi, Rike; Prathama, Sebastian; Wibisono, Agus Purnomo (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Catfish (Pangasius sp.) belly, a by-product of the frozen fish fillet industry, has certain processing limitations, thereby reducing product utilization and selling value. It is a potential process for producing products with highl market acceptance. The study aimed to investigate the relationship between the chemical characteristics of a catfish belly in various smoking methods and its sensory profile. Various smoking methods in this research include smoking cabinets, vertical offset smokers, traditional smoking houses, and liquid smoke, which had different parameters of time, temperature, and distance to the smoke source. The chemical characteristics of smoked catfish belly were determined in terms of proximates, total phenols, and total acid. The sensory profiles in the form of intensity of 8 attributes of smoked catfish belly were obtained using the Rate-All-That-Apply method accompanied by a hedonic test (n = 80). Different smoking parameters in each method greatly influence the chemical characteristics and sensory profiles produced. Methods with longer smoking times will produce lower water content, increasing the fat content and a strong smoky aroma and taste. The correlation between chemical characteristics, sensory profile, and hedonic was also analyzed using Partial Least Square Regression (PLS regression) to determine the relationship with the stomach of smoked catfish belly using various methods. Of all the methods, the smoking cabinet was the optimal method for processing smoked catfish belly.